The Strength of MS Media and Sterilization Technique on Red Dragonfruit (Hylocereus polyrhizus) Seed Germination - Hawalina Kasim; Yusran Yusran; Zainuddin Basri (AGROLAND The Agricultural Sciences Journal (e-Journal), 2015)
This research aimed to findout efficient sterilization method and MS media to germinate dragonfruit seeds in vitro, conducting at Biotechnology Laboratory, Agriculture Faculty, Tadulako University, using factorial completely randomized design. The first factor was sterilization technique (S), i.e: S1 (The sliced fruit was washed with sterile distilled water three times, then rinsed in Bayclin (household bleach containing 5.25% NaOCl) 5% for 15 minutes, followed by washing in sterile distilled water three times. S2 (The seeds were taken from the fruit meat, then rinsed in 5% Bayclin for 15 minutes, then washed with sterile distilled water three times. S3 (The seeds were taken from the fruit meat, then rinsed in 15% Bayclin for 15 minutes, then washed with sterile distilled water three times. The second factor was the strength of MS media (M), i.e full strength MS (M1) and half strength MS for macro and micro nutrients (M2). Each treatment combination consisted of 35 seeds, and was replicated three times. Germination responses were observed as time to germinate, germination percentage and percentage of opened cotyledone seedlings. All datas were subjected to Analysis of Variance and the mean differences among the treatments were analyzed using Honest Significant Difference (HSD) at the level of 1%. The results showed that removing seed pulp, prior to rinsing the seeds in 15% Bayclin for 15 minutes followed by washing in sterile aquadest three times, and cultured in half MS produce the fastest and highest seed germination of 99.05% with 92.38% opened cotyledon seedlings after 2 weeks in culture